Host‐Guest Chemistry in Binary and Ternary Complexes Utilizing π‐Conjugated Carbon Nanorings - Fan, Yanqing; He, Jing; Guo, Shengzhu; Jiang, Hua (ChemPlusChem (Weinheim, Germany), 2024)
The carbon nanorings, possessing a radial π system, have garnered significant attention primarily due to their size‐dependent photophysical properties and the presence of a unique curved π‐conjugated cavity. This is evidenced by the rapid proliferation of publications. Furthermore, the integration of building blocks into CPP skeletons can confer [n]CPPs with novel and exceptional photophysical and electronic characteristics, as well as chiral properties and host‐guest interactions, thereby augmenting the diversity of [n]CPPs. Notably, the curved π surface structures and concave cavity of carbon nanorings enable them to host aromatic or non‐aromatic guests with a complementarily curved surface, resulting in interesting binary or ternary complexes. This review provides a comprehensive treatment of literature reports on binary and ternary complexes, focusing on both their host‐guest interactions and properties. It is important to note that the scope of this review is limited to host‐guest chemistry in binary and ternary complexes based on π‐conjugated carbon nanorings. Carbon nanorings with unique curved π‐conjugated cavity are able to host aromatic or non‐aromatic guests with a complementarily curved surface, resulting in the formation of interesting binary or ternary complexes. This review comprehensively covers literature reports on binary and ternary complexes based on π‐conjugated carbon nanorings, providing a thorough treatment of the subject.